Prevalence of Epilepsy with Autosomal Recessive Intellectual Disability in Consanguineous Families - Usmanullah, Ajmal Khan Bazai, Abdul Wadood Kakar, Muhammad Hanif, Shazia Ramzan, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Intellectual disability (I.D) is the limitation of cognitive impairment and decreased ability of learning of a person. It is a type of neurological genetic disease, which results in incomplete or retarded/ arrested development of the brain. I.D is one of the most common health problem worldwide. These patients have decreased intellectual functions and at least limitation in their two adoptive skills such as writing or reading abilities, communication ability and self-care etc. While epilepsy is a neurodevelopment disease presented as abrupt & episodic recurrence of sensory disturbance, loss of consciousness or convulsions, related with the abnormality of electrical activities in the brain. Epilepsy is an illness of CNS that result in abnormal brain activity, causing periods of unusual behavior or seizures, loss of awareness, and sometimes sensations. Methods: This study was done from April 2014 to February 2016. The inclusion criteria for these patients were consanguineous families with two or more than two effected persons. All the I.D patients and their families were interviewed one by one. Blood samples were collected under hygienic method. Each patient were examined thoroughly and noted the points with the help of different proformas. Collected blood collection were stored in laboratory. After DNA extraction ,PCR was done. After extraction exome sequencing process used to find the pathogenic /effected variants. CATCH used for the analyzed of data. Sanger Sequencing was applied to note the segregation. Results: In ID-family1 the variant of AP4B1 was segregated with the disease phenotype. Mutation in AP4B1 is known to cause intellectual disability. In ID-family2 the variants of WDR62, EML2 and KCNK6 were co-segregated with diseased phenotype. But only changes in WDR62 which is known as a cause of intellectual disability. These patients also have symptoms of epilepsy. In ID-family3 exome sequencing data reveal no putative variants. Conclusion: This study was done in three consanguineous families to determine the responsible mutant genes for the disorder of intellectual disability. Their Exome sequencing showed putative mutations in AP4B1 and WDR62 in two out of three families. In third family we could not locate any putative mutation.